A retrospective study of the results of the best portuguese female gymnasts in a period of 40 years - Pereira, A.; Faro, A.; Stotlar, D.; Fonseca, A. M. (International Journal of Sports Science, 2013)
The main objective of this study was to determine whether the Portuguese female gymnasts who achieved the highest results at senior level had also obtained results equally important in the early stages of their sporting careers, looking further to analyze the possible relation between those results would be different depending on the representativeness of the results achieved in seniors. Additionally, it also was purpose of this study to examine the longevity of their sporting careers, considering the times in which they obtained their first and the latest high-level sport results. To this end, it were analyzed the paths of all female gymnasts (n = 67) who represented the national team of Portugal in official competitions at senior level between 1971 and 2011 and formed three groups, depending on the highest level of international competition they represented Portugal. In general, when considering the results of all the gymnasts seemed evident that, throughout their different stages of their sport careers, almost all succeeded places in the top six places in the overall classification of nationwide competitions in all age groups. However, the results also showed that athletes who have reached the highest sport results in the highest stage of their careers (i.e., participating in the Olympic Games) had already obtained better results than their competitors at the beginning of their careers. Similarly, it was found that the sports careers of these athletes showed the longest periods between the first and the last high level sports results. These results seem therefore stress the importance of paying attention to athletes who excel early, as well as for the benefit of developing programs for detection and selection of talent in early ages, at least in artistic gymnastics. However, it is also important to alert to the need to know precisely how many are the gymnasts who, despite having shown talent at an early stage of their sporting careers, achieving outstanding sporting results, cannot later maintain that athletic performance in later stages of their careers.